Synthesis of biodegradable cellulose-chitin polymer blend film - Poblete, Myra Ruth S. (College of Engineering, University of the Philippines Diliman, 2013)
Synthetic plastics is considered to be a vital gift of technology to man. However, their resistance to physical, chemical and biological degradation results to various environmental problems including waste disposal. Thus, there is a huge opportunity to produce a biodegradable plastic of enhanced formability and durability by blending chitin and cellulose, the most abundant naturally occurring polymers in the environment. Formability involves the establishment of dissolution, blending and forming techniques to obtain a biodegradable film. Durability was measured in consideration of the target application, i.e., food packaging industry. Using the previously established procedure of demineralization and deproteinization, chitin was extracted from the carapace of blue swimming crab (Portunus pelagicus) shells, a waste material from industrial crab processing plants, at a mass yield equal to 3.26%. XRD analysis and thermal degradation experiments conducted on the extracted chitin suggested that there are still other protein molecules aside from chitin, of negligible amount, retained even after the deproteinization step. The extracted chitin was blended with cellulose by polymer solution mixing using the LiC1/DMAc solvent system at a constant solid to liquid ration. A film of the polymer blend was generated by allowing the polymer gels to form and by employing cold-press technique adapted from a related study. The effect of chitin content, forming time, and source of chitin, i.e. extracted or commercially acquired, on the tensile strength of the film was determined. From the analysis of variance at 95% confidence level, it ws found that only the interaction between chitin source and chitin content ws found to have significant effect on the mechanical properties of the polymer blend. The best processing condition, which gave the highest tensile strength at 44.76 MPa, was that of 80% commercially available chitin formed in glass mold for 24 hours, cold-pressed then dried overnight at 60⁰C. In terms of the other properties that would support the application as food packaging material, the blend form commercially-sourced chitin showed the most favorable response. It had the higher degradation temperature at 339.38⁰C, lower moisture regain at 32.35% wet basis after 4 days, and is more degraded after the 100-day biodegradation run.